1997
DOI: 10.1364/ao.36.005608
|View full text |Cite
|
Sign up to set email alerts
|

Clinical imaging fluorescence apparatus for the endoscopic photodetection of early cancers by use of Photofrin II

Abstract: A fluorescence imaging device applied to the detection of early cancer is described. The apparatus is based on the imaging of laser-induced fluorescence of a dye that localizes in a tumor with a higher concentration than in the surrounding normal tissue after iv injection. Tests carried out in the upper aerodigestive tract, the tracheobronchial tree, and the esophagus with Photofrin II (1 mg/kg of body weight) as the fluorescent agent are reported as examples. The fluorescence is induced by violet (410-nm) lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The Pentax system works with a single range detection principle, 20 whereas a multiple range approach has been preferred for the Xillix and the Storz systems 19,32 and some laboratory systems. 8,17,18 It is interesting to note that our results are in good agreement with these previous results. Indeed, we also found that the autofluorescence of the early cancerous lesions sharply decreases when excited in the blue-violet range and decreases less significantly in the red region.…”
Section: Typical Autofluorescence Spectrasupporting
confidence: 93%
See 3 more Smart Citations
“…The Pentax system works with a single range detection principle, 20 whereas a multiple range approach has been preferred for the Xillix and the Storz systems 19,32 and some laboratory systems. 8,17,18 It is interesting to note that our results are in good agreement with these previous results. Indeed, we also found that the autofluorescence of the early cancerous lesions sharply decreases when excited in the blue-violet range and decreases less significantly in the red region.…”
Section: Typical Autofluorescence Spectrasupporting
confidence: 93%
“…However, the changes occurring during the first stages of the cancerization process make it difficult in most cases for the endoscopist to accurately localize the lesions under white light illumination. Several examples of the use of light-induced fluorescence ͑LIF͒ have been proposed for point fluorescence measurements and imaging applications with [4][5][6][7][8] and without 4,[9][10][11][12][13][14][15] the addition of an exogenous drug to enhance the contrast between the early cancerous lesion and the healthy surrounding area. 16 Because they rely upon the natural fluorescence of the tissues, the latter are termed ''autofluorescence'' methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past 15 years its diagnostic potential has been tested in different organs of the body, including the mouth, breast, esophagus, and bladder, etc. [9][10][11][12][13][14][15][16][17] Diagnosis of human breast cancer through fluorescence studies has been an active area of research for quite some time. Although more than 80% of breast lumps are not cancerous, biopsy is the only way to diagnose.…”
Section: Introductionmentioning
confidence: 99%